Process debottlenecking of small scale liquefied natural gas (LNG) plant - Nurul Ain, Ramli (2009)
Process debottlenecking is one of a process improvement and particularly important when the current conditions of a plant reaches maximum production rate without satisfying market demands. In the case of liquefied natural gas (LNG), transcontinental demands always show steady increment. Since LNG is a source of clean energy and a feedstock to chemical productions, process debottlenecking of existing LNG plants offers economic benefits. In this research, the first objective was to perform process debottlenecking of a published flow sheet of a small scale LNG plant by using Aspen HYSYS. “Bottlenecks” or unit operations which reach bottlenecked conditions were identified by increasing the inlet flow rate. Simulation results showed that, LNG heat exchanger 2 was the single bottlenecked unit operations identified due to the occurrence of temperature cross. The bottlenecks removal was then performed by transferring duty of this active bottleneck to an additional cooler installed. Five different modifications were designed which installation of a cooler at different stream in the flow sheet and applied. Modification 5 showed the highest percentage of LNG production with 5298.68% increment from the existing plant. Production revenue for this modification is RM 2552098.60 after takes into consideration the highest cost of its additional cooling duty which is RM 400000.00. General economic benefits for this work need to be further analyzed so that the importance of process debottlenecking of LNG plant become more comprehensive.